Research: understanding the theory of journalism (Colombian contributions) - Osório Vargas, Raul Hernando (Brazilian journalism research, 2015)
The history of journalism is a field of contacts and loans. For this reason, research in journalism has and brings a broad and complex agenda, including: the process of news production, its language construction through different forms, structures and tenses. The methodology, epistemology and qualitative research in journalism; the history of journalists and journalism; i.e., the multiple relationships between journalism and culture, memory, social theories and discourse; fields that have been studied and researched in Latin America. But the question on our professional Ethos is what remains the transverse axis of the research, not only in the American continent, but in the world. It is fundamental to our existence and to the depth analysis of this set of features and modes, behaviors, that make up the character and identity of our profession.